2019
DOI: 10.1016/j.micromeso.2019.109668
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metakaolinization and fused-metakaolinization on zeolites synthesized from quartz rich natural clays

Abstract: The effects of metakaolinization and fused-metakaolinization on zeolites synthesized from quartz rich natural clays

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…Incorporation of magnetite is expected to ameliorate the surface characteristics of the clay and ease the recovery of the dye-bearing adsorbent by an external magnetic field. (Otieno et al 2019), and the mineralogical phases confirmed by XRD analysis.…”
Section: Introductionmentioning
confidence: 89%
“…Incorporation of magnetite is expected to ameliorate the surface characteristics of the clay and ease the recovery of the dye-bearing adsorbent by an external magnetic field. (Otieno et al 2019), and the mineralogical phases confirmed by XRD analysis.…”
Section: Introductionmentioning
confidence: 89%
“…Over 100 natural zeolites can be distinguished, among which only several types, like clinoptilolite or phillipsite, are accessible for mining and further use. On the contrary, over 150 types of synthetic zeolites have been obtained so far, using various substrates, for example chemicals [ 18 ], clay minerals [ 19 , 20 , 21 ], silicate minerals [ 22 ], rice husk [ 23 , 24 ], or wastes like fly ash (carbon combustion byproduct) [ 9 , 25 , 26 , 27 ]. The use of fly ash to produce zeolites is attracting many enthusiasts because that is one way to minimize waste and is beneficial to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of Y zeolite from the raw clay significantly enhanced the surface area and micropore volume from 29 m 2 /g and 0.0016 cm 3 /g to 745 m 2 /g and 0.251 cm 3 /g respectively (Table 3). The synthesized Y zeolite exhibited a pronounced surface area when compared to synthesized Y zeolite in other studies ranging from 346 to 758 m 2 /g [23,34,36,37,39]. Figure 5b shows that the zeolite has two size range micropores-the inner pores of size 0.88 nm and the outer pores 1.84 nm, both corresponding to micropore volume of 0.251 cm 3 /g.…”
Section: Y Zeolite Crystallizationmentioning
confidence: 75%
“…5a). This corresponds to microporous material and the filling of narrow micropores [36,37]. This characteristic of zeolitic material is due to enhanced adsorbent-adsorbate interactions occurring in micropores of molecular dimensions [38].…”
Section: Y Zeolite Crystallizationmentioning
confidence: 99%